Case Report: A Rare Orbital Abscess Caused by Dacryocystitis After Administration of Rebamipide Ophthalmic Suspension - Imamura, Hitoshi; Eguchi, Hiroshi; Sakamoto, Masuo; Hotta, Fumika; Tabuchi, Hitoshi; Kusaka, Shunji (Frontiers in Medicine, 2021)
Background: Rebamipide ophthalmic suspension was launched in Japan in 2012 and is used for the treatment of dry eye. Case presentation: We report two cases of orbital abscess, which resulted from dacryocystitis that occurred after administration of rebamipide ophthalmic suspension. Computed tomography images showed an eyeball deformity in one case and exophthalmos in the other. In both cases, light microscopy, scanning electron microscopy and energy dispersive X-ray examinations revealed lacrimal sac concretions, which contained calcium phosphate crystals that were surrounded by microorganisms. Lacrimal sac concretion removal from the lacrimal sacs during dacryocystorhinostomies was performed on both patients. Although the postoperative outcome was favourable in one case, vision was lost in the other case due to the development of retinal artery occlusion as a complication of the orbital abscess, despite lacrimal sac concretion removal and administration of antimicrobials. Conclusions: This is the first case report to highlight that rebamipide ophthalmic suspension can cause an orbital abscess via development of lacrimal sac concretion. Ophthalmologists should be aware that rebamipide ophthalmic suspension might induce the formation of concretion in the lacrimal sac.